2011
DOI: 10.1007/s11626-011-9385-8
|View full text |Cite
|
Sign up to set email alerts
|

DMSO regulates osteoclast development in vitro

Abstract: Dimethyl sulfoxide (DMSO) is routinely used in the laboratory as a solvent and vehicle for organic molecules. Although it has been used in previous studies involving myeloid cells and macrophages, we are unaware of data demonstrating the effects of DMSO alone on osteoclast development. Recently, we were using DMSO as a vehicle and included a non-vehicle control. Surprisingly, we observed a marked change in osteoclast development, and therefore designed this study to examine the effects of DMSO on osteoclast de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…Although Lemieux et al (2011) reported inhibition of formation of osteoclasts by DMSO in vitro for the first time, our study is the first to reveal mechanistic details. In addition to the osteoclastinhibiting property, DMSO (1 % concentration) is also known to enhance osteoblastic differentiation of murine preosteoblastic MC3T3-E1 cells and the mineralization of primary osteoblasts of human origin (0.35-1 % concentration) (Cheung et al 2006;Stephens et al 2011).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Although Lemieux et al (2011) reported inhibition of formation of osteoclasts by DMSO in vitro for the first time, our study is the first to reveal mechanistic details. In addition to the osteoclastinhibiting property, DMSO (1 % concentration) is also known to enhance osteoblastic differentiation of murine preosteoblastic MC3T3-E1 cells and the mineralization of primary osteoblasts of human origin (0.35-1 % concentration) (Cheung et al 2006;Stephens et al 2011).…”
Section: Discussionmentioning
confidence: 73%
“…Lemieux et al (2011) reported enhancement of osteoclastogenesis at 5 μM DMSO concentration while reporting inhibition of osteoclastogenesis at concentration of 20 μM. However, these authors used an osteoclast progenitor cell line derived from the spleens of Pax5 -/-mice and primary bone marrow-derived macrophages obtained from B6 mice, while we utilized a conventional murine model system of RAW 264.7 cells as osteoclast precursors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al [2008a] and Kim et al [2011], specify that DMSO was used as the carrier. It has been demonstrated that osteoclast differentiation is sensitive to low concentrations of DMSO [Lemieux et al, 2011], and it is possible that it might have synergistic effects with bioactive molecules, like luteolin. In the present work we used ≥98% pure luteolin (Sigma catalog no.…”
Section: Discussionmentioning
confidence: 99%